Pressurization and depressurization phases inside the plumbing system of Mount Etna volcano: Evidence from a multiparametric approach. Issue 9 (11th September 2015) - Cannata, Andrea; Spedalieri, Giancarlo; Behncke, Boris; Cannavò, Flavio; Di Grazia, Giuseppe; Gambino, Salvatore; Gresta, Stefano; Gurrieri, Sergio; Liuzzo, Marco; Palano, Mimmo
Abstract: During 2013 Mount Etna volcano experienced intense eruptive activity at the summit craters, foremost at the New Southeast Crater and to a minor degree at the Voragine and Bocca Nuova (BN), which took place in two cycles, February–April and September–December. In this work, we mainly focus on the period between these cycles, applying a multiparametric approach. The period from the end of April to 5 September showed a gradual increase in the amplitude of long‐period (LP) events and volcanic tremor, a slight inflation testified by both tilt and GPS data, and a CO2 flux increase. Such variations were interpreted as due to a gradual pressurization of the plumbing system, from the shallowest part, where LP and volcanic tremor are located, down to about 3–9 km below sea level, pressure source depths obtained by both geodetic and CO2 data. On 5 September, at the same time as a large explosion at BN, we observed an instantaneous variation of the aforementioned signals (decrease in amplitude of LP events and volcanic tremor, slight deflation, and CO2 flux decrease) and the activation of a new infrasonic source located at BN. In the light of it, the BN explosion probably caused the instantaneous end of the pressurization, and the opening of a new vent at BN, that has become a new steady source of infrasonic events. This apparently slight change in the plumbing system also led to the gradual resumption of activity at the New Southeast Crater, culminating with the second lava fountain cycle of 2013. Key Points: Multiparametric approach is effective to investigate plumbing system pressurization‐depressurization It was shown how shallow explosion can modify the volcano conditions down to several kilometers below sea level It was shown how depressurization quickly propagated downward triggering uprises of magma/gas